Estudo de métodos para a dispersão de nanopartículas de níquel e ferro em suspensão - Zoccal, João Victor Marques (Universidade Federal de São Carlos, 2015)
In recent decades, several studies have been conducted on the generation of materials at the nanoscale, not only by offering possible risks when inhaled, but also by the various applications that can be employed. Among the various equipment used for the generation of particles, atomizers generators have proved efficient and economical. Although many studies have used materials in solution, in which the material is dissolved in the solvent, generation of particles, it has been observed growing interest in the study of suspended nanometric materials, in which there is dispersion in the solvent. In addition, this growing interest in the suspended study materials is due to the need to generate solid aerosols from oxides, since they have high added value and important to be recaptured and intended back into production. Given the presented work aimed to disperse nanoparticles from suspensions, evaluating the time of the generation process over a period of 10 hours, for different equipment. The nanoparticles were generated by atomization of nickel and iron oxides suspensions at different concentrations and the atomization process were used three generator, a generator from TSI, model 3079, a commercial inhaler of the brand NS, model I-205 and a fluidized bed generator, model 3400. The size distribution and concentration of particles was determined by a Scanning Mobility Particle Sizer (SMPS), Model 3936 and a Aerodynamic Particle Sizer (APS), Model 3320, both from TSI, being sampled directly from the aerosol. The results relating to the dispersion of nanoparticles from the suspension of nickel and iron oxide proved effective in 10 hour period. However, TSI generator showed a dispersion of particles with a more uniform distribution, whereas the commercial inhaler dispersed a greater number of particles per cm3. In addition, the collection of particles by APS, there was the generation of micrometric particles, since the particles are already being generated aglomeradamente, which was observed in SEM and TEM images.
Keywords: Partículas nanométricas suspensas; Óxido de níquel; Óxido de ferro; Métodos de geração; SMPS; Suspended nanometric particles; Generation methods; Nickel oxide; Iron oxide; ENGENHARIAS::ENGENHARIA QUIMICA